Pengaruh Kedisiplinan Belajar Dan Partisipasi Dalam Interaksi Edukatif Terhadap Prestasi Belajar Ekonomi Pada Siswa Kelas XI IPS SMA N 1 Banyudono Tahun Ajaran 2015/2016 - Yuliyanto, Yuliyanto; , Drs. Nur Chusni, SE.,M.Ag; , Drs. Sudarto, M.M (2016)
Yuliyanto, A210120043. Effect of Discipline Learning and Participation in Educational Interaction Against Learning Achievement Economics Students of Class X1 Ips In SMA Negeri 1 Banyudono. Study Program of Accounting Education, the Faculty of Education, University of Muhammadiyah Surakarta, July 2016 This study aims to determine: 1) Effects of learning discipline of learning achievement, 2) Effect of participation in educational interaction on learning achievement, 3) Effect of learning discipline and participation in educational interaction on learning achievement. This study is the type of study population by drawing conclusions through statistical methods. The population in this study is a class XI student of SMAN 1 Banyudono ips. totaling 89 students. Necessary data obtained through questionnaires and documentation. The questionnaire previously tested and tested for validity and reliability test. Data analysis technique used is multiple linear regression analysis, t-test, F, koefisiens determination (R ²), discordant relative (SR) and the effective contribution (SE). The results of the regression analysis obtained regression equation: Y = 62.875 + 0,214X1 + 0,199X2 .. The equation shows that learning achievement is influenced by the discipline of learning and participation in educational interaction. The conclusions drawn are: 1) Discipline A Learning on learning achievement received. It is based on regression analysis (t test) note that tcount> ttable is 3.870. > 1.989 and the significance value <0.05 is 0.008 with effective contribution (SE) of 18.3%. 2) Participation in educational interaction on learning achievement is acceptable. It is based on regression analysis (t test) note that tcount> ttable is 3.871.> 1.989 and the significance value <0.05 is 0,000 with partial determination coefficient of 18.2%. 3) Discipline learning and participation in educational interaction on learning achievement is acceptable. This is based on multiple regression analysis of variance (F test) note that Fcount> Ftable is 24.730> 3.11 and a significance value <0.05 is 0.000. 4) The coefficient of determination (R2) of 0.365 indicates that the influence of learning discipline and participation in educational interaction on learning achievement economy is 36.5% while the rest influenced by other variables. Keywords: Discipline learning, participation in educational interaction, academic achievement